2014
DOI: 10.1111/1469-0691.12797
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus and interferon type III (interferon-λ3/interleukin-28B and interferon-λ4): genetic basis of susceptibility to infection and response to antiviral treatment

Abstract: There has been a significant increase in our understanding of the host genetic determinants of susceptibility to viral infections in recent years. Recently, two single-nucleotide polymorphisms (SNPs), rs12979860 T/C and rs8099917 T/G, upstream of the interleukin (IL)-28B/interferon (IFN)-λ3 gene have been clearly associated with spontaneous and treatment-induced viral clearance in hepatitis C virus (HCV) infection. Because of their power in predicting the response to IFN/ribavirin therapy, the above SNPs have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 79 publications
(87 reference statements)
0
21
0
Order By: Relevance
“…According to these reports, we can conclude that in some regions and racial groups including Iran and China, polymorphism at rs8099917T/G was not associated with spontaneous HCV infection clearance, but in other areas such as the United States, Europe (13), Brazil (17), and Morocco (34) this polymorphism affects HCV infection outcome. An association between this polymorphism and response to therapy in patients infected with HCV was reported in some studies (11,35).…”
Section: Discussionmentioning
confidence: 73%
“…According to these reports, we can conclude that in some regions and racial groups including Iran and China, polymorphism at rs8099917T/G was not associated with spontaneous HCV infection clearance, but in other areas such as the United States, Europe (13), Brazil (17), and Morocco (34) this polymorphism affects HCV infection outcome. An association between this polymorphism and response to therapy in patients infected with HCV was reported in some studies (11,35).…”
Section: Discussionmentioning
confidence: 73%
“…IFNγ binds to a heterodimeric receptor, IFNGR1/2, and coordinates a wide array of cellular programs through transcriptional regulation of immunologically relevant genes. Type III IFNs are a recently identified class belonging to the IFN system, including four subtypes, IFNλ1-4 [18,19]. Among type III IFNs, IFNλ4 expression and production are controlled by a dinucleotide polymorphism known as IFNL4 rs368234815 (ΔG/TT) located in exon 1 of IFNL4, and IFNλ4 protein can be produced only by individuals carrying the functional genetic variant IFNL4-ΔG allele [20].…”
Section: Ifn Systemmentioning
confidence: 99%
“…Besides the analysis of these genetic variants related to the IFN response in HIV-1-positive patients, few studies have looked at the type III IFNs SNPs so far. IFNλ3/IL28B has attracted much attention from HCV researchers because in 2009 genome-wide association studies identified an association between certain SNPs located in the upstream region of IFNλ3 and both spontaneous and IFN treatment-induced viral clearance in chronic HCV infection [5,19]. Interestingly, the original SNP (rs12979860) identified near IFNλ3 has now been positioned within an intron of the gene encoding the newly discovered IFNλ4 [20].…”
Section: Host Factorsmentioning
confidence: 99%
“…It should also be mentioned that the very recent discovery of a dinucleotide polymorphism ss469415590 TT/DG upstream of IL28B/IFN lambda 3, which generates the novel IFN lambda 4 (variant allele, DG) protein, may reveal an alternative scenario to understand the functional architecture of type III IFN genomic regions and its influence on the outcome of HCV infection, and also to identify the relationship between endogenous ISG upregulation and poor response to IFN alpha treatment [91]. As the IFN lambda 4 creating allele DG is correlated with the unfavorable rs12979860 allele T, ss469415590 TT was a better predictor of HCV clearance than rs12979860, and a role of ss469415590 TT in predicting response to anti-HCV therapy with or without IFN has been reported (for a review see [92]). Interestingly, carriers of the IFN lambda 4 creating DG allele were found to have significantly higher amounts of ISG mRNA than patients homozygous for the disruptive TT allele [93].…”
Section: Host Determinantsmentioning
confidence: 99%